Detection of cystine and cysteine in wheat flour using a robust LC-MS/MS method - Dogan, Canan Ekinci; Cebi, Nur; Develioglu, Aysen; Olgun, Elmas Oktem; Sagdic, Osman (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2018)
An effective and simultaneous liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed for the first time, with the aim of quantification of cysteine and cystine in wheat flour. Developed LC-MS/MS method showed good linearity (R-2 = 0.99) with very low LOD and LOQ values as 2.0 mu g/kg and 7.0 mu g/kg for cystine, 3.0 mu g/kg and 8.0 mu g/kg for cysteine, respectively. Favorable repeatability and reproducibility were achieved. Developed highly sensitive LC-MS/MS method was successfully applied for the detection and quantification of cystine and cysteine in wheat flour samples. Cystine and cysteine contents were determined as quite similar and appropriate for 25 types of wheat flour. In addition, method has great capability for quantification of additional cysteine and cystine in the wheat flour since quite favorable recovery values were obtained.
Keywords: Cystine; Cysteine; Bakery; Chromatography; Tandem mass; Flour; Wheat; SIMULTANEOUS QUANTIFICATION; Food Science & Technology